The Development of Obstacle Adventure Game Model for Physical Education - Firgiawan Fahrizal; Mugiyo Hartono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Research on the Development of the Obstacle Adventure Game Model aims to be an alternative to learning Physical Education, Sports and Health (PJOK) in elementary school students at SD Negeri Tuwel 01, Bojong District, Tegal Regency. The method used in this study is Research and Development (R&D) referring to the development of Borg and Gall. The research subjects consisted of 16 1st grade students for small-scale trials and 40 2nd graders for large-scale trials. The research instruments include questionnaires, observations, interviews and documentation. The validation results of game expert lecturers, social service experts and learning experts showed the percentage of eligibility of 78%, 78% and 80%, respectively with the feasible category. In the results of the product revision then increased to 83%, 85%, 82% with the category of very feasible. The test for students showed a percentage of 89% results in small-scale trials and increased to 92% in large-scale trials. These results show that the Obstacle Adventure Game Model is suitable for use as an alternative to PJOK Learning because it is able to make students more active in learning activities and create an interesting, challenging and fun learning atmosphere.